Pengembangan Instrumen Penilaian Kinerja Perawatan Kendaraan Hybrid (Universitas Pendidikan Indonesia, 2024)
This research aims to develop a hybrid vehicle maintenance performance assessment instrument in hybrid vehicle technology learning, and produce a hybrid vehicle maintenance performance assessment instrument in hybrid vehicle technology learning. This research is included in research and development (research and developmental). To get a valid, practical, and effective research and development product, it must go through the stages of the right study theory procedure. The research and development model in this study refers to the 4-D development model from Thiagarajan. The 4-D model research design is systematic, detailed and based on the theoretical basis of educational product design so as to produce products that have feasibility standards, besides the 4-D research model requires researchers to test the effectiveness of the products produced before being disseminated. The content validity test is processed by conducting instruments to experts. In this study, the validation process was carried out by 5 experts, namely 1 lecturer and 4 certified hybrid vehicle expert technicians. Content validity testing is carried out on 34 indicators based on the results of the description of the learning outcomes in the independent curriculum, which then each item has a CVR value based on the experts' assessment as presented in table 4.6. Based on the results of the CVI analysis, the assessment instrument is declared valid because it has a value of 0.88.